A Study of the Correlation between Students’ Moodle Log for Content and the Other Forms of Engagement on Moodle for a Mandatory Pre-Degree English Course (American Journal of Interdisciplinary Research and Innovation, 2023)
This study investigates students’ Moodle log on content on LLFXX Moodle page and correlates it with the students’ Moodle logs for the other forms of engagement (instructor, other learners, assessments and feedback from assessments). 80 students from a mandatory English language course at pre-degree level at the USP participated in the research. These students were enrolled in LLFXX in Blended mode at the Laucala campus in the Fiji Islands. Data on students’ Moodle logs were extracted from LLFXX Moodle page and were analysed using the SPSS software. Pearson’s chi-square test was used to find the correlation between students’ Moodle log on content on LLFXX Moodle page and their academic achievements. Pearson’s Product Moment Correlation Coefficient test was used to find the p value and r value to determine the statistically significant bivariate association and strength of association between students’ Moodle log on content and the other forms of engagement on LLFXX Moodle page. The findings reflect the importance of content and engagement with content. It also emphasises the need to be vigilant with the quality and quantity of content placed on the course Moodle page.